APLIKASI E-LUNAS PBB BERBASIS WEB PADA BADAN PENGELOLAAN PAJAK DAN RETRIBUSI DAERAH KABUPATEN HULU SUNGAI TENGAH - Haderiansyah - (KOMNET : Jurnal Komputer, Jaringan dan Internet, 2026)
the Development of Information Technology has had a significant impact on increasing the effectiveness and efficiency of services in various government agencies, including the management of local tax administration. The Regional Tax and Retribution Management Agency (BPPRD) of Hulu Sungai Tengah Regency still faces obstacles in managing Land and Building Tax (PBB) data, which is done manually, often resulting in data loss, difficulties in searching archives, as well as delays in presenting information and reporting. These conditions cause the service process to the community to be less than optimal. This research aims to design and build a Web-Based PBB E-Lunas Information System that can assist in data collection processes, payment management, taxpayer data searches, and report preparation quickly, accurately, and integrated. This system is expected to minimize errors caused by human factors (human error), increase data storage security through the use of databases, and support more effective and efficient public services. The expected result of this research is the creation of a web-based application that can facilitate BPPRD officers in managing Land and Building Tax data in real-time, improve the quality of service to taxpayers, and provide accurate information and reports as a basis for decision-making.